Obstacles & Solutions If A Legal Agency Administration System in Process of Restruction of A Limited Company - Fitriani Machbub; Ahmad Khisni; Amin Purnawan (Sultan Agung Notary Law Review, 2021)
The purpose of this study is to explain how the obstacles and solutions if they occur in the legal entity administrative system in the Limited Liability Company approval process. This writing uses the juridical empirical research method by extracting information from interviews and data from literature studies. The data used in this study are secondary data which includes primary legal materials. Based on this research, it can be concluded that the Registration of Limited Liability Companies using the Legal Entity Administration System has obstacles and has disadvantages for its users, one of which is the website system itself, where the pages on the website are off or busy with the network, so the process will take a long time until hours due to slow access.